Keragaman genetik ikan tuna sirip kuning (Thunnus albacares) dari dua populasi di Laut Maluku, Indonesia - Nebuchadnezzar Akbar; Neviaty P Zamani; Hawis H Madduppa (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
Abstract. Yellowfin tuna (Thunnus albacores) is a large, pelagic, and migratory species of tuna that inhabits Moluccas Sea in Indonesia, and most sea environment worldwide. However, high fishing activities tend to happen in the Indonesia region and catch product appear to be decreasing. A better understanding of yellowfin tuna genetic diversity is required to plan better conservation strategy of tuna. The study was conducted to infer the genetic diversity of yellowfin tuna (T. albacores) in the Moluccas Sea. A total of 41 tissue samples of yellowfin tuna were collected from two regions in the Moluccas Sea (North Moluccas and Ambon) during an expedition in February 2013. The results showed that genetic diversity and nucleotide diversity of yellowfin tuna from North Moluccas population was 0.984 and 0.021, respectively; while in Ambon population, the genetic and nucleotide diversities were 1.00 and 0.018, respectively. The high genetic diversity (0.990) and nucleotide diversity (0.020) between two populations were observed. Based on phylogenetic analysis, no genetic differentiation between the two populations in Moluccas Sea was revealed .Keywords : Population genetics; Haplotype diversity; Coral Triangle; Phylogenetics; Polymerase Chain Reactions (PCRs) Abstrak. Tuna sirip kuning (Thunnus albacores) adalah ikan komersial penting dan ditemukan di Laut Maluku, Indonesia. Tetapi, aktivitas penangkapan ikan tuna sirip kuning dapat menurunkan kualitas dan kuantitas stok ikan, sehingga perlu adanya pengkajian keragaman genetik ikan tuna sirip kuning. Pemahaman yang baik tentang keragaman genetika dibutuhkan untuk merencanakan strategi konservasi tuna yang lebih baik. Penelitian ini bertujuan untuk mengetahui keragaman genetik ikan tuna sirip kuning dari dua populasi di Laut Maluku. Sebanyak 41 sampel jaringan dari tuna sirip kuning dikumpulkan dari dua populasi di Laut Maluku (Maluku Utara dan Ambon) selama ekspedisi pada bulan Februari 2013. Hasil penelitian menunjukkan bahwa keragaman genetik populasi tuna sirip kuning pada perairan Maluku Utara dan Ambon masing-masing sebesar 0,984 dan 1,00 sedangkan nilai keragaman nukleotida masing-masing bernilai 0,021 dan 0,018. Nilai keragaman genetik dan keragaman nukloetida yang tinggi didaptkan antar kedua populasi masing-masing sebesar 0,990 dan 0,020. Berdasarkan analisis filogenetik, dua populasi di Laut Maluku ini memiliki kedekatan secara genetik.Kata kunci : Genetika populasi; Keragaman haplotipe; Segitiga Terumbu Karang; Filogenetika; Polymerase Chain Reaction (PCR)